Examining the Effectiveness of Interventions for Criminal Justice-Involved Women: A Meta-Analytic Review - Summers, Richard (Criminal justice and behavior, 2025)
Academic understanding of women’s gendered pathways into the criminal justice system has grown significantly over the last 20 years. Allied to this development has been an increasing number of gender-responsive practices and interventions designed to address the needs of criminal justice-involved women. This meta-analysis summarizes the trends in 71 interventions extracted from 64 papers involving justice-involved women. Subgroup analysis and meta-regression were used, which shows that gender-responsive interventions are up to 42% more effective compared with gender-neutral, even when controlling for several covariates. Other findings in our case demonstrate features of interventions, such as intervention, format, focus, and length, that appear to be effective in reducing recidivism for criminal justice-involved women. Our findings strengthen the case for investment in gender-responsive interventions and diversion programs.